Creativity with purposes? that something only you can do - Hamdan, Efina; Abdullah, Siti Nur Fadzilah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Writer’s block is a common struggle, especially when facing deadlines or trying to stay active on social media. In contrast, Artificial Intelligence (AI) never runs out of ideas and can generate content like essays, copywriting, or even scripts in seconds. This makes AI a highly convenient and efficient tool for content creation. However, while AI can mimic writing, it lacks personal touch, emotion, and cultural understanding unique to each individual. AI doesn't know your voice, values, or experiences. Moreover, since AI learns from vast online data, it can also inherit existing biases and stereotypes. These may include outdated norms, gender roles, and racial or cultural assumptions. Users must remain critical when using AI-generated content. AI is a helpful assistant but not a perfect substitute for human creativity and authenticity.